THE EFFECTIVENESS OF LAW ENFORCEMENT AGAINST THE PERPETRATORS OF TOURISM OBJECT VANDALISM IN NORTH TORAJA - Salamba, Yogistry Pakita (YURIS: Journal of Court and Justice, 2024)
This research aims to analyze the implementation of sanctions against perpetrators of tourism site vandalism in North Toraja; and to examine the constraints on the application of sanctions in law enforcement against perpetrators of tourism site vandalism based on Regional Regulation No. 7/2016. This research uses empirical research methods, using statutory approaches and conceptual approaches. Primary data is obtained through field research using interview and observation methods, while secondary data is obtained through literature study. The results indicated that the enforcement of sanctions of Regional Regulation No. 7/2016 on the Implementation of Tourism in North Toraja has not complied with the regulation. Moreover, the case of Ke’te’ kesu’ vandalism committed by perpetrators who are sanctioned by custom, is characterized by many unresolved cases and weak enforcement of sanctions. The constraints in the implementation of sanctions in law enforcement are mostly caused by delayed information to the Civil Service Police Unit so that initial administrative actions are conducted before handing over to the Prosecutor’s Office. Another constraint is the absence of a MoU between the Police, Prosecutor’s Office, and Courts, and limited budget which affects the capacity of Civil Service Police Unit (Satpol PP) in protecting tourists. A comprehensive approach is needed, which includes training of law enforcers, inter-agency coordination, legal education for the community, and a review of local regulations to enhance justice and appropriateness of sanctions.